Women of Influence: interdisciplinary participatory approaches to understanding female leadership in the Peruvian Amazon. - (:unkn) unknown (New Area Studies, 2024)
The Mujeres que influyen (Women of Influence) project is a collaboration between researchers at University of East Anglia and PUCP, and young women from the Junín area of Peru who are members of the National Council of Indigenous Women of Peru. It takes...
Keywords: Liderazgo femenino; Amazonía peruana